Yaf9, a Novel NuA4 Histone Acetyltransferase Subunit, Is Required for the Cellular Response to Spindle Stress in Yeast - Le Masson, Ivan (American Society for Microbiology, 2003)
Yaf9 is one of three proteins in budding yeast containing a YEATS domain. We show that Yaf9 is part of a large complex and that it coprecipitates with three known subunits of the NuA4 histone acetyltransferase. Although Esa1, the catalytic subunit of NuA4, is essential for viability, we found that yaf9Δ mutants are viable but hypersensitive to microtubule depolymerizing agents and synthetically lethal with two different mutants of the mitotic apparatus. Microtubules depolymerized more readily in the yaf9Δ mutant compared to the wild type in the presence of nocodazole, and recovery of microtubule polymerization and cell division from limiting concentrations of nocodazole was inhibited. Two other NuA4 mutants (esa1-1851 and yng2Δ) and nonacetylatable histone H4 mutants were also sensitive to benomyl. Furthermore, wild-type budding yeast were more resistant to benomyl when grown in the presence of trichostatin A, a histone deacetylase inhibitor. These results strongly suggest that acetylation of histone H4 by NuA4 is required for the cellular resistance to spindle stress.